If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 = 7z + 4 Reorder the terms: 46 = 4 + 7z Solving 46 = 4 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. 46 + -7z = 4 + 7z + -7z Combine like terms: 7z + -7z = 0 46 + -7z = 4 + 0 46 + -7z = 4 Add '-46' to each side of the equation. 46 + -46 + -7z = 4 + -46 Combine like terms: 46 + -46 = 0 0 + -7z = 4 + -46 -7z = 4 + -46 Combine like terms: 4 + -46 = -42 -7z = -42 Divide each side by '-7'. z = 6 Simplifying z = 6
| 0.8d+0.4=-5.2 | | 3(y+6)-8(5y-6)=-37y+4 | | 10x-23+6x+11=180 | | 2x+6=9x^2 | | 7(y+3)=-2(2y-3)+5y | | 7x+6y=54 | | 4k-8=12+2k | | 4(4x+4)-12= | | 2x^2+15x=6x+35 | | -4(3+7r)=-124 | | -2(1-5x)=-12+5x | | 3-4y=2x | | 15f-2=43 | | d+3d+(3d+10)=135 | | 9b-5=-77 | | -8(n-4)=88 | | 2x^4+3x^2-9=0 | | 2(x+5)-4x=24 | | F(x)=x^2-10x-16 | | 5(x-2)+4x=-82 | | -6+2n=n-6(1-6n) | | 5y-7x+15=0 | | 4(u-5)-6=-4(-6u+4)-8u | | x^3+3x^2-37x-15=0 | | 4y-3=-5 | | 2z-3(z+1)=-(5z+6)+z | | 8x+4(4x-3)=4(6x+4)-41 | | 4a-5=2a | | 2(5n-8)-5n=2(3n-4) | | 4(n+5)=7(n+8) | | n+1-3n=-(5+n)+1-2n | | 7z-3=32 |